A new species of Hydrocyphon Redtenbacher, 1858 (Coleoptera: Scirtidae) from Kopet Dagh Mountains - Ruta, Rafa (Zootaxa, 2007)
Hydrocyphon kopetdaghensis, a new scirtid species from Kopet Dagh Mts., is described and illustrated. The distribution of the Hydrocyphon australis-group is discussed and illustrated. Remarks on the Hydrocyphon species-groups are provided.